Transmastoid resurfacing versus middle fossa plugging for repair of superior canal dehiscence: Comparison of techniques from a retrospective cohort. Issue 3 (1st September 2016) - Rodgers, Brian; Lin, Jim; Staecker, Hinrich
Abstract: Objective: To compare and contrast our experience with middle cranial fossa approach (MFR) and transmastoid approach with capping of the dehiscence (TMR) of superior semicircular canal dehiscence and to determine guidelines to help guide management of these patients. Methods: All patients from 2005 to 2014 with symptomatic superior semicircular canal dehiscence syndrome with dehiscence demonstrated on CT scan of the temporal bone who underwent surgical repair and had a minimum 3 months of follow up. Surgical repair via the MFR or TMR, preoperative CT temporal bone, preoperative, and postoperative cervical vestibular evoked myogenic potential (cVEMP) testing and anterior canal video head thrust testing (vHIT). Success of repair was stratified as complete success, moderate success, mild success, or failure based on resolution of all symptoms, the chief complaint, some symptoms, or no improvement, respectively. Results: A total of 29 ears in 27 patients underwent surgical repair of canal dehiscence. Complete or moderate success was seen in 71% of the MFR group compared to 80% of the TMR group. There were zero failures with the MFR group and no major intracranial complications. There were 2 failures out of 15 ears that underwent the TMR. Residual symptoms were most commonly vertigo or disequilibrium in the MFR and aural fullness or autophony in the TMR groups, respectively. MFR hospital stay was approximately 2 days longer. Average cVEMP threshold shifted 18 dB with surgical correction in the MFR group. A 29 dB average shift was seen in the TMR group. The MFR group had a significant reduction in their anterior canal gain compared to the TMR group. Conclusions: TMR is a less invasive alternative to MFR. However, in our series, we have not seen any intracranial complications (aphasia, stroke, seizures, etc.) in our MFR patients. Interestingly, vestibular symptoms were better addressed than audiological symptoms by the TMR suggesting its usefulness as a less invasive option for patients with primarily vestibular complaints. Residual auditory symptoms in TMR patients may be due to the flow of acoustic energy from the superior canal to the mastoid cavity through an incompletely sealed third window.